Rancang Bangun Aplikasi Game Virtual Reality Berbasis Android Bertema Petualangan - Dian Gustina; Karno Diantoro; Felicia Meyke Ulfah Maharani (Jurnal Ilmiah FIFO, 2019)
Technology is one part that can not be separated from human life. Various fields in human life have been greatly welcomed by technology, computer technology first. Virtual Reality (VR) is a new way to explore the virtual world. With virtual reality, the user seemed to be entering a new environment in the virtual world. The vastness of the virtual world can provide many advantages to produce a variety of fun entertainment. "My Journey My Adventure" is a game with a genre of first person shooter genre (FPS) that can be played by all people spent to be able to survive with modest stamina and a short time. This application is created using 3D unity and SDK as the main software. The stages in this research include discussing problems, initial planning, design and design, testing and implementation. And for system modeling languages using UML (Unified Modeling Language). This application was created as a medium of entertainment for each player by using Virtual Reality (VR) which allows players to experience more real difficulties such as those in games and introduce virtual reality technology. System testing shows that not all Samsung smartphones can activate this virtual reality game, and also on the application quality test that shows it. This application has a weight of 44.7 which corresponds to the "very good" category.